1985
DOI: 10.1037/0012-1649.21.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in children's perceptions of aggression and withdrawal in their peers.

Abstract: This study examined age-related changes in the organization underlying children's ratings of social deviance in their peers. Peer ratings of aggression, withdrawal, and likeability using the Pupil Evaluation Inventory (PEI) were collected from 326 first graders, 356 fourth graders, and 298 seventh graders. Measures of the . perceived similarity of all possible pairs of PEI items were derived by computing the frequency with which children at each grade level were concurrently nominated by their peers for both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
2
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 13 publications
7
76
2
2
Order By: Relevance
“…It is also possible that younger children might have differentiated more on a free-sorting task with the cartoons, rather than a verbal labeling task, as was used in this study. However, the present finding is consistent with that of Younger et al (1985Younger et al ( , 1986, who also used MDS techniques and found a progressive differentiation in 6-, 9-, and 12-year-olds' perceptions of classmates in terms of aggression, likeability, and withdrawal.…”
Section: Discussionsupporting
confidence: 94%
“…It is also possible that younger children might have differentiated more on a free-sorting task with the cartoons, rather than a verbal labeling task, as was used in this study. However, the present finding is consistent with that of Younger et al (1985Younger et al ( , 1986, who also used MDS techniques and found a progressive differentiation in 6-, 9-, and 12-year-olds' perceptions of classmates in terms of aggression, likeability, and withdrawal.…”
Section: Discussionsupporting
confidence: 94%
“…A long history of research comparing children's understandings of aggression and withdrawal supports the conclusion that over the elementary school years, children come to view aggression and withdrawal as increasingly distinct (Coie and Pennington, 1976;Maas et al, 1978;Younger et al, 1985Younger et al, , 1986; see also Heyman and Gelman, 2000). There is also evidence that withdrawal becomes more salient to children as they get older (Younger and Boyko, 1987;Younger and Piccinin, 1989).…”
Section: Children's Reasoning About Aggression and Withdrawalmentioning
confidence: 88%
“…Younger et al, 1985; see also Heyman and Gelman, 2000)? It might be that the use of simple stories in the present study served to emphasize distinctions between characteristics, as compared to other methodologies.…”
Section: Reasoning About Aggression Versus Withdrawalmentioning
confidence: 97%
“…submission) are unlikely to emerge as a significant predictor for peer victimisation in younger children [Hanish and Guerra, 2000]. This is because young children are not skilled at recognising submissive behaviour [e.g., Younger and Boyko, 1987;Younger et al, 1985]. Thus, future studies could address these issues of age differences in risk, and work towards developing a developmentally appropriate model.…”
Section: Discussionmentioning
confidence: 99%